The Significance Of Using Literary Texts In Efl Classrooms - Daira, Salah (جامعة الوادي - University of Eloued, 2020)
Literature plays a critical role in the English Language classroom as it offers learners a space to justify, comment and mirror their language learning. Numerous studies have indicated that the use of literary texts within the EFL classrooms has potential advantages which include enhancing language skills and extending linguistic knowledge. This paper extensively explores the importance of literary texts within the English language classroom at university. It concludes that literary texts provide students with a rich and varying linguistic input that helps students to effectively express themselves. It also discusses the relevance of including English literature as a language teaching tool in the EFL university classroom. More specifically, it focuses on showing how research enriches the learning experience of EFL learners.
مقال
Keywords: Literary Texts ; English Language Skills ; EFL ; Classroom ; University ; Language Teaching tools